efectuati 10+2x{86-5x[3+3x(9-2x3)]}
Răspunsuri la întrebare
Răspuns de
2
12×{86-5×[3+3×(9-6)]}=12×{86-5×[3+3×3]}=12×{86-5×[3+9]}=12×{86-5×12}=12×{86-60}=12×26=312
Sper ca te-am ajutat.
Sper ca te-am ajutat.
azertyuiop:
ms
Răspuns de
1
10+2×{86-5×[3+3×(9-2×3)]}=
10+2×[86-5×(3+3×3)]=
10+2×(86-5×12)=
10+2×26=
10+52=62.
10+2×[86-5×(3+3×3)]=
10+2×(86-5×12)=
10+2×26=
10+52=62.
Alte întrebări interesante
Istorie,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Geografie,
9 ani în urmă
Limba română,
9 ani în urmă